2016
DOI: 10.1021/acs.chemmater.6b01374
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Growth Mode of 3D Silver Nanocrystal Superlattices by Triphenylphosphine

Abstract: International audienceHere, we show that the residual presence of reaction products markedly influences the growth mode of 3D superlattices made of silver nanocrystals. The silver nanocrystals (5 or 6 nm in diameter) are synthesized via the reduction of a silver triphenylphosphine complex in the presence of thiols. The presence of triphenylphosphine, coming from the decomposition of the silver precursor, is shown to change the superlattice growth mode in hexane from heterogeneous to homogeneous. In toluene, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 64 publications
(106 reference statements)
1
20
0
Order By: Relevance
“…Nevertheless, the SLs shapes are better defined, with the appearance of triangular shaped SLs, for higher NP sizes and for SC NPs. These well-defined shapes are characteristic of homogeneous growth in solution that could be favored by an increase in NP-NP interactions between larger NPs due to larger van der Waals interactions or between SC NPs due to the presence of larger facets [44,45]. Furthermore, previous results showed that the nature of the interactions between NPs (attractive or repulsive) depend both on the nature of the capping agent and the van der Waals attractions between the cores for a given solvent [44,45].…”
Section: Aumentioning
confidence: 86%
“…Nevertheless, the SLs shapes are better defined, with the appearance of triangular shaped SLs, for higher NP sizes and for SC NPs. These well-defined shapes are characteristic of homogeneous growth in solution that could be favored by an increase in NP-NP interactions between larger NPs due to larger van der Waals interactions or between SC NPs due to the presence of larger facets [44,45]. Furthermore, previous results showed that the nature of the interactions between NPs (attractive or repulsive) depend both on the nature of the capping agent and the van der Waals attractions between the cores for a given solvent [44,45].…”
Section: Aumentioning
confidence: 86%
“…As the most commonly used ligands, alkylthiol (e.g., propanethiol, hexanethiol, decanethiol, dodecanethiol, and hexadecanethiol, etc.) has been used to rationally construct 2D hexagonal closely packed superlattices and 3D superlattices with various lattice structures. With the right control over the superlattice assembly kinetics such as flux of particles into the interface ( f ) and interfacial diffusion length (δ), it is possible to form 2D freestanding superlattice membranes …”
Section: Molecule Mediated Nanoparticle Superlatticementioning
confidence: 99%
“…On the one hand, if a very poor solvent, such as toluene, is used, one can hardly disperse the particles in solution, as they easily form large SCs and precipitate, even before laser light illumination. On the other hand, in mixture of poor and good solvents a compromise between limiting NP aggregation (toluene, poor solvent) and solubilization (hexane, good solvent) , can be reached, resulting in the formation of SCs (consisting of arrangement of NPs). Prior environmental transmission electron microscopy (TEM) studies have shown that, in 60% toluene, SCs of radius of ∼100–300 nm spontaneously form in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, a proof of concept of this idea is provided. Narrowly distributed 5.9 ±0.4 nm silver NPs that are capped with dodecanethiol (C 12 AgNP) spontaneously organize in organic solvents into nanometric SCs . The interaction of the C 12 chains with the solvent also generate migration toward the laser beam, driving the SCs together under the laser spot, forming a micrometric aggregate, as indicated in Figure A.…”
mentioning
confidence: 99%